Combinatorial chemistry and technologies : (Taylor & Francis, 2005)
Several books on the market cover combinatorial techniques, but they offer just a limited perspective of the field, focusing on selected aspects without examining all approaches and integrated technologies. Combinatorial Chemistry and Technologies: Methods and Applications answers the demand for a complete overview of the field, covering all of the methodologies used in the design, synthesis, and screening of molecular libraries. Now in its second edition, this volume updates prior content and explores new areas such as catalysis, applications in biotechnology, and current ICS-UNIDO activities. Topics include the generation of molecular diversity by chemical methods using solution- and solid-phase chemistries, biological approaches for the production and screening of peptides, antibody and oligonucleotide libraries, and the application of computer-assisted approaches to guide library synthesis. The book establishes the link between combinatorial chemistry and molecular modeling and illustrates the importance of economics and patenting in combinatorial technologies. Valuable to technologists and researchers as an introductory survey on the many aspects of combinatorial chemistry and combinatorial technology, Combinatorial Chemistry and Technologies: Methods and Applications offers an overview of a field that promises broad applicability in the identification of new drugs, as well as in diagnostics, new materials, and catalysis.